Leucine-rich diet alters the eukaryotic translation initiation factors expression in skeletal muscle of tumour-bearing rats - Ventrucci, Gislaine; Mello, Maria Alice R. [UNESP]; Gomes-Marcondes, Maria Cristina C. (Springer Nature, 2007)
Background: Cancer-cachexia induces a variety of metabolic disorders on protein turnorver, decreasing protein synthesis and increasing protein degradation. Controversly, insulin, other hormones, and branched-chain amino acids, especially leucine, stimulate protein synthesis and modulate the activity of translation initiation factors involved in protein synthesis. Since the tumour effects are more pronounced when associated with pregnancy, ehancing muscle-wasting proteolysis, in this study, the influence of a leucine-rich diet on the protein synthesis caused by cancer were investigated. Methods: Pregnant rats with or without Walker 256 tumour were distributed into six groups. During 20 days of experiment, three groups were fed with a control diet: C - pregnant control, W - tumour-bearing, and P - pair-fed, which received the same amount of food as ingested by the W group; three other groups of pregnant rats were fed a leucine-rich diet: L - pregnant leucine, WL - tumour-bearing, and PL - pair-fed, which received the same amount of food as ingested by the WL group. Results: The gastrocnemius muscle of WL rats showed increased incorporation of leucine in protein compared to W rats; the leucine-rich diet also prevented the decrease in plasma insulin normally seen in W. The expression of translation initiation factors increased when tumour-bearing rats fed leucine-rich diet, with increase of ∼35% for eIF2α and eIF5, ∼17% for eIF4E and 20% for eIF4G; the expression of protein kinase S6K1 and protein kinase C was also highly enhanced. Conclusion: The results suggest that a leucine-rich diet increased the protein synthesis in skeletal muscle in tumour-bearing rats possibly through the activation of eIF factors and/or the S6kinase pathway. © 2007 Ventrucci et al; licensee BioMed Central Ltd.
Keywords: actin; initiation factor; initiation factor 2alpha; initiation factor 4E; initiation factor 4G; initiation factor 5; insulin; leucine; protein kinase C; serum and glucocorticoid regulated kinase 1; animal experiment; animal model; animal tissue; controlled study; dietary intake; enzyme activation; female; gastrocnemius muscle; insulin blood level; male; malignant neoplastic disease; nonhuman; pregnancy; protein expression; protein synthesis; rat; skeletal muscle